Peran Pemerintah dan Partisipasi Masyarakat dalam Peningkatan Usaha Mikro, Kecil, dan Menengah (UMKM) pada Masa Pandemi COVID-19 di Cipageran, Cimahi - Tumija Tumija (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2022)
Micro, Small and Medium Enterprises (UMKM) are activities that support the national economy. However, since the Covid-19 hit in Indonesia, businesses in UMKM in Cimahi City have been affected by an average of 40%. The purpose of this research and study-based community service activity is to find out the role of the Cimahi city government and community participation in improving UMKM businesses. The method used in this research and study-based community service activity is Participatory Action Research (PAR). This method is carried out after the author explains the material, followed by community participation in the form of discussion and sharing. The results of the discussion of community service activities in Cimahi City that the role of the Cimahi City government is good in accordance with Gede Diva's theory and PP No. 7 of 2021. This can be seen from several facilities and infrastructure such as the Technopark Building as a place for UMKM training, then facilitation of digital marketing training, HR training, product development training. Furthermore, the role of the community (UMKM actors) has been active in participating in meetings organized by the relevant agencies in planning activity programs and is active in activities and has taken advantage of the results of the activities. From the results of the discussion, it can be concluded that the Cimahi City government has carried out three roles as facilitator, regulator and catalyst and the community has actively participated in planning, implementing and utilizing results in increasing UMKM.